(untitled) (Journal of the College of Education for Women, 2018)
My study here is about the (possible for itself) features especially in the (Alashaira) opinion, also I touch to the other logicians opinions, I clarified these features concisely in the preface to be clear in front of the reader, I made it in two studies and five subjects.I talked about the meaning of the existence in the ((possible for itself) theme, and I clarified its types in the logicians and the philosophers’ opinions, through which the existence and the nonexistence are equal in it, as it cannot be existed nor be nonsexist unless with a separated reason, and there is no necessity to oblige its existence, or its nonexistence is impossible.Then I talked about the outweighing of the (possible for itself) as one side of the existence or the nonexistence, with mentioning the proofs about it, and present the deniers suspicions and reply against them, also I mentioned the (Alashaira) and the other logicians’ sayings in the needing the world to the creator, does the (happening) is the (Alashaira) and ( Almatazila) logicians’ majority opinion, or the (possibility) which is the opinion of the philosophers’ and some latest’s of the (Alashaira).